Small RNA-Omics for Plant Virus Identification, Virome Reconstruction, and Antiviral Defense Characterization - Pooggin, Mikhail M. (Frontiers in Microbiology, 2018)
RNA interference (RNAi)-based antiviral defense generates small interfering RNAs that represent the entire genome sequences of both RNA and DNA viruses as well as viroids and viral satellites. Therefore, deep sequencing and bioinformatics analysis of small RNA population (small RNA-ome) allows not only for universal virus detection and genome reconstruction but also for complete virome reconstruction in mixed infections. Viral infections (like other stress factors) can also perturb the RNAi and gene silencing pathways regulating endogenous gene expression and repressing transposons and host genome-integrated endogenous viral elements which can potentially be released from the genome and contribute to disease. This review describes the application of small RNA-omics for virus detection, virome reconstruction and antiviral defense characterization in cultivated and non-cultivated plants. Reviewing available evidence from a large and ever growing number of studies of naturally or experimentally-infected hosts revealed that all families of land plant viruses, their satellites and viroids spawn characteristic small RNAs which can be assembled into contigs of sufficient length for virus, satellite or viroid identification and for exhaustive reconstruction of complex viromes. Moreover, the small RNA size, polarity and hotspot profiles reflect virome interactions with the plant RNAi machinery and allow to distinguish between silent endogenous viral elements and their replicating episomal counterparts. Models for the biogenesis and functions of small interfering RNAs derived from all types of RNA and DNA viruses, satellites and viroids as well as endogenous viral elements are presented and discussed